Curb your enthusiasm. The complete second season [videorecording (DVD)] - David, Larry (Home Box Office, 2004)
Larry David has it all - money, security, famous friends, a nurturing wife, and an oceanfront home. So why is he so intent on making a mess out of his life? Contains all 10 episodes from season two.